Russian cyber operations : coding the boundaries of conflict - Jasper, Scott (Georgetown University Press, 2020)
Russia's brazen use of cyber operations to interfere in elections, conduct information warfare and as part of its ongoing conflicts with neighboring states has made international headlines. However they have also maintained a thin veneer of deniability and have avoided clear red lines that would be widely accepted as acts of war. While cyber operations possess the means to achieve mischievous, subversive and potentially destructive effects, how is an injured state supposed to respond? Scott Jasper seeks to bring clarity to this problem by undertaking an in-depth look at the legal and technical aspects of actual Russian cyber operations. He puts Russia's use of cyber in the context of their military and information warfare doctrines and looks at examples from the 2016 US presidential election, the 2017 NotPetya mock ransomware attack, the 2017 French presidential election, and many more. Jasper proposes deterrence, defense, resilience, and cost-imposition responses and offsetting strategies for the United States and other states who have been on the receiving end of these attacks. This book will make a major contribution to helping scholars, students, and the national security community understand Russian cyber competition and how to respond.